Pengaruh Pelaksanaan Teaching Factory dan Motivasi Kerja terhadap Kesiapan Kerja - Syarifah, Nur Afni; Rijanto, Tri; Anifah, Lilik (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
The research conducted aims to (1) analyze the effect of implementing a teaching factory on the work readiness of class XII DKV students at SMK Negeri Surabaya; (2) analyze the influence of work motivation on the work readiness of class XII DKV students at SMK Negeri Surabaya. The method used in this research is ex-post facto research, which observes and studies the influence between the independent and dependent variables. The subjects of this research were students in class XII DKV at SMK Negeri Surabaya, totaling 204 students. The results of this research show that (1) there is an influence of the implementation of the teaching factory on students' work readiness (2) There is an influence of work motivation on students' work readiness with significance. From the hypothesis test results, the dominant variable is work motivation on work readiness. The following variable is the teaching factory implementation variable on work readiness.